2019
DOI: 10.1002/ccr3.2100
|View full text |Cite
|
Sign up to set email alerts
|

A case of adenomyoepithelioma with myoepithelial carcinoma of the breast

Abstract: Key Clinical Message Adenomyoepithelioma with myoepithelial carcinoma of the breast is rare and diagnosed with histology and immunohistochemistry. We present a case of malignant transformation over 10 years, with ultrasonographic findings, highlighting the importance of an early excisional biopsy. Conservative surgery and radiation therapy were performed. There was no recurrence for 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…There are no clear treatment guidelines for AME. Lumpectomy with a safety margin or quadrantectomy is often performed, and total mastectomy is sometimes performed for large or suspected malignant tumors[ 5 , 6 , 8 , 11 - 13 , 16 ]. Incomplete resection or malignant transformation is a risk factor for local recurrence, but it is important to note that local recurrence can occur even with clearly negative margins in a benign lesion, as observed in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…There are no clear treatment guidelines for AME. Lumpectomy with a safety margin or quadrantectomy is often performed, and total mastectomy is sometimes performed for large or suspected malignant tumors[ 5 , 6 , 8 , 11 - 13 , 16 ]. Incomplete resection or malignant transformation is a risk factor for local recurrence, but it is important to note that local recurrence can occur even with clearly negative margins in a benign lesion, as observed in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…There are no clear treatment guidelines for AME. Partial mastectomy is often performed, but total mastectomy is sometimes performed for large or suspected malignant tumors [6]. Axillary lymph node metastases are rare, and only a few cases of axillary dissection have been reported [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…There may be recurrences even after complete resection with partial mastectomy, as in the present case, and they should be carefully monitored. Ito et al concluded that, based on previous reports, total mastectomy is often performed for tumors larger than 3 cm [6]. It will become clearer as more cases are reported which patients should undergo total mastectomy, and whether reconstruction is possible after resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMEs are usually difficult to diagnose and need an experimented pathologist and the using of immunohistochemistry. Sometimes they can be misdiagnosed when the core needle biopsy doesn´t encompass both the epithelial and myoepithelial components [ 1 ]. The management usually consists of a lumpectomy or wide excision if the size is under 3 cm, whereas a mastectomy with axillary lymph node resection is usually performed when the size is bigger [ 1 ].…”
Section: Introductionmentioning
confidence: 99%